The nemaline myopathy-causing E117K mutation in β-tropomyosin reduces thin filament activation. - Karpicheva, O; Robinson, P; Piers, A; Borovikov, Y; Redwood, C (2013)
The effect of the nemaline myopathy-causing E117K mutation in β-tropomyosin (TM) on the structure and function of this regulatory protein was studied. The E117K mutant was found to have indistinguishable actin affinity compared with wild-type (WT) and similar secondary structure as measured by circular dichroism. However the E117K mutation significantly lowered maximum activation of actomyosin ATPase. To explain the molecular mechanism of impaired ATPase activation, WT and E117K TMs were covalently labeled at Cys-36 with 5-iodoacetimido-fluorescein and incorporated into ghost muscle fibers. The changes in the position and flexibility of tropomyosin strands on the thin filaments were observed at simulation of weak and strong binding states of actomyosin at high or low Ca(2+) by polarized fluorescence techniques. The E117K mutation was found to shift the tropomyosin strands towards the closed position and restrict the tropomyosin displacement during the transformation of actomyosin from weak to strong binding state thus leading to a reduction in thin filament activation.